Constructing a measure for self-perceived open organizational culture in a university hospital pharmacy - Rietdijk, Wim J. R.; Maljaars-Hendrikse, Madzy; van Dijk, Monique; Malik, Romana F.; Tan, Ngoc; van der Kuy, P. Hugo M. (Frontiers in Medicine, 2024)
Background An open organizational culture in the workplace represents an environment where information, ideas, and feedback are freely exchanged among all members, regardless of position or rank. Currently, there are no valid survey instruments to measure this culture within a healthcare context. To address this gap, we developed a survey instrument to measure self-perceived open organizational culture at a university pharmacy using a test re-test study design. Methods Data were collected during classroom training on basic mediation skills study. Participants completed the same questionnaire before (test phase) and after the training (validation phase). The questionnaire included statements assessing open organizational culture. The data were analyzed using standardized psychometric methods, including correlations, Exploratory Factor Analysis (structural validity), and construct validity by correlating the open organizational culture scores with the Interpersonal Communication Inventory. Results In the test phase, 191 participants (161 females, 84%; response rate = 39.7%) contributed to the initial construction of the self-perceived open organizational culture survey instrument. In the validation phase, 81 of the original respondents completed the questionnaire again. Three latent factors were identified, retaining 22 of the 37 items: “enabling systems” (7 items), “open behavior” (8 items), and “trusting and supporting coworkers” (7 items). High correlations were found among the three factors (r > 0.6), and between these factors and the Interpersonal Communication Inventory (r > 0.35). Cronbach’s alphas were all above 0.85, indicating good internal consistency. During the validation phase, the factors demonstrated high internal consistency, test/re-test correlations, and agreement. Conclusion This study presents a 22-item survey instrument for measuring individual differences in self-perceived open organizational culture within a university hospital pharmacy. The instrument demonstrates internal consistency and construct validity. Further validation of its psychometric properties and testing in other healthcare departments are recommended.